Serological detection of Toxoplasma gondii, Leishmania infantum and Neospora caninum in cats from an area endemic for leishmaniasis in Brazil - Keyla Carstens Marques de Sousa; Heitor Miraglia Herrera; Iara Helena Domingos; João Bosco Vilela Campos; Isabela Maria Campanelli dos Santos; Haroldo Henrique Neves; Rosangela Zacarias Machado; Marcos Rogério André (Revista Brasileira de Parasitologia Veterinária, 2014)
An investigation was made into the occurrence of antibodies to Toxoplasma gondii, Leishmania infantum and Neospora caninum in 151 domestic cats, based on the indirect fluorescent antibody test (IFAT). Serum samples were collected from 151 domestic cats (65 free-roaming and 86 domiciled cats; 55 males and 96 females) in Campo Grande, Mato Grosso do Sul, Brazil between January and April 2013. IgG antibodies to T. gondii, L. infantum and N. caninum were found, respectively, in 49 (32.5%), 34 (22.5%) and 10 (6.6%) sampled cats. A positive correlation was found between T. gondii and N. caninum, T. gondii and L. infantum, and N. caninum and L. infantum (p <0.05) infections. Also, a significant interaction was identified between gender and area of activity on the probability of T. gondii (p = 0.0324) infection. However, no significant interaction was observed between gender and area of activity on infections by either N. caninum or L. infantum. This study showed that cats from an area endemic for visceral leishmaniasis in Brazil are exposed to three different protozoans, two of which are causal agents of important zoonosis.